2007
DOI: 10.1002/crat.200610795
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic studies on two new organic NLO materials: L‐threonine and L‐prolinium tartrate

Abstract: Photoacoustic spectroscopy (PAS) is a non-destructive testing (NDT) tool and used here for analyzing the physical properties such as thermal diffusivity, thermal diffusion length, thermal conductivity and thermal effusivity of L-Threonine and L-Prolinium tartrate. These two crystals belong to a group of recently developed NLO materials, in our laboratory. The single crystals of the two compounds were grown by using submerged seed solution growth method. Characterization of the crystals was made by using single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Single crystal of L-proline shows no center of symmetry and its NLO coefficients have been examined by Boomadevi et al [10]. Martin Britto Dhas et al [11] have reported that the second harmonic generation (SHG) efficiency of L-prolinium tartrate is 90% of that of standard potassium dihydrogen orthophosphate (KDP) crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Single crystal of L-proline shows no center of symmetry and its NLO coefficients have been examined by Boomadevi et al [10]. Martin Britto Dhas et al [11] have reported that the second harmonic generation (SHG) efficiency of L-prolinium tartrate is 90% of that of standard potassium dihydrogen orthophosphate (KDP) crystals.…”
Section: Introductionmentioning
confidence: 99%
“…It is a non-invasive and non-destructive method; the analyzed samples do not require prior preparation to be characterized. By this technique it is possible to obtain optical and thermal properties as optical absorption coefficient, thermal diffusivity and thermal effusivity (Satour and Zegadi, 2020; Mandelis, 1983; Lamastra et al, 2018 ; Britto Dhas et al, 2007 ), including also complex materials that contain different structures and layers ( Hernandez-Aguilar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Simulations work has been performed on copper and gold nanowires for which a crystal to amorphous phase transition has been observed . In the present context, we have opted for l -threonine crystal so as to understand the phase stability at dynamic shock wave loaded conditions, since it is one of the familiar hydrogen bonded amino acid crystals as well as technologically important materials for nonlinear optical applications. Hence, it would be better to perform high-pressure and low-temperature experiments to realize the better suitability of the material for non-ambient condition applications. On the one hand, there are quite a few articles available on l -threonine crystal to understand the crystal growth and their characterizations at ambient conditions. On the other hand, there are only a few research publications available in order to comprehend the phase stability of the title crystal at high-pressure and ion irradiation conditions.…”
Section: Introductionmentioning
confidence: 99%